파생상품사용과 이익관리가 한국기업의 환노출관리성과에 미치는 영향 - 권택호(Taek Ho Kwon); 박종원(Jong Won Park) (한국증권학회지, 2013)
본 연구에서는 2005년부터 2010년의 표본기간 동안 한국거래소의 유가증권시장에 상장된 제조기업의 자료를 이용하여 파생상품사용과 이익관리가 기업의 환노출관리성과와 어떤 관계를 갖는지를 분석하였다. 본 연구는 두 수단 중 어느 한편에 초점을 맞춘 기존연구와는 달리 두 수단을복합적으로 고려하여 파생상품사용 또는 이익관리가 환노출관리의 성과에 미치는 영향을 검증하였다는 점에서 기존연구와 차별성을 갖는다. 환노출관리의 성과는 기업이 영업활동에서 부담하는 환노출(예측환노출)과 재무적 헤징 활동의 성과가 반영된 후의 사후적인 환노출(관찰환노출)의 차이로측정하였다. 연구결과를 간단히 요약하면 다음과 같다. 첫째, 기업이 처한 환노출포지션의 구분없이분석한 결과는 이익관리가 환노출관리성과에 크게 기여하지 못했음을 보여준다. 반면, 파생상품사용은 환노출관리에 긍정적으로 기여하였다. 둘째, 파생상품사용이 환노출관리성과에 미치는 긍정적인 관계는 주로 영업활동에서의 환노출포지션이 (+)인 기업들에서 나타난 결과이다. 반면, 환노출포지션이 (-)인 기업들의 경우 재량적 발생액을 이용한 이익관리가 환노출관리에 유용한 수단으로작용하며, 여러 종류의 파생상품사용은 환노출관리성과에 부정적인 영향을 미침을 보여준다. 이는수출기업과 같이 영업활동에서 부담하는 환노출포지션이 (+)인 기업과 수입기업과 같이 환노출포지션이 (-)인 기업이 선택하는 환노출관리수단이 차별적임을 보여주는 것이며, 파생상품사용과 이익관리라는 두 수단이 기업이 처한 환노출포지션에 따라 비대칭적으로 선택됨을 의미한다. 셋째, 파생상품사용은 2008년 금융위기 전후 기간 모두에서 환노출관리에 효과적이나, 금융위기 전기간의경우 여러 종류의 파생상품사용은 환노출관리성과에 부정적인 영향을 미쳤으며, 우리 기업들의파생상품사용 패턴은 금융위기 이후 기간에 큰 변화가 있었음을 보여준다. We test the effects of firm’s derivatives hedging and earnings management on foreign exchange rate (FX) exposure using the data of KOSPI firms from 2005 to 2010. This study is distinguished from previous studies in two ways: we measure the expected FX exposure (an ex-ante exposure from firm’s operation activity) and the observed FX exposure (an expost exposure from the stock market) separately, and also consider both derivatives hedging and earnings management to analyze the effectiveness of a firm’s activities for FX exposure management. The main empirical results are as follows: First, derivatives hedging contributes to reducing the firm’s exposure while earnings management does not. Second,if we classify total sample into the positive expected FX exposure sample and the negative expected FX exposure sample, the positive effect of derivatives hedging is found in the firms with positive expected exposure, while earnings management using discretionary accruals is a useful tool to the firms which have negative expected exposure. This implies that managers select the derivatives hedging and the earnings management asymmetrically according to their expected FX exposure. Finally, using many types of derivatives is negatively related with the hedging effects during the period before the 2008financial crisis. This result suggests that Korean firms used too many kinds of derivatives than they needed in this period. KCI Citation Count: 8